Gaze tracker parameters have little association with visual field metrics of intrasession frontloaded SITA‐Faster 24–2 visual field results - Phu, Jack; Kalloniatis, Michael (Ophthalmic & physiological optics, 2022)
Purpose To determine the usefulness of Humphrey Field Analyser (HFA) SITA‐Faster 24–2 gaze tracker outputs on interpreting intra‐visit visual field (VF) result pairs. Methods Analysis of 1380 right–left eye pairs and 1432 pairs of test 1‐test 2 intrasession VF results of patients seen within a university‐based glaucoma service was undertaken to understand gaze deviation distributions. Output gaze tracker results were aggregated into total ticks, sum of amplitudes and average amplitudes. Correlations between visual field indices (mean deviation [MD], “events” and overall hill of vision) and independent variables (age and test order) were performed using one eye from each subject. Results There was no association of test order (right–left, test 1‐test 2) with eye movements. There was a significant, but weak correlation between eye movements and age (r = 0.16). Correlations of eye movements with MD were driven by more severe MD values. There were no significant correlations between intrasession difference in eye movements and the change in MD, number of “events” and hill of vision, or in the root mean square of sensitivity and total deviation values. There was also no significant correlation between gaze tracker outputs and another commonly used “reliability” metric, false positive rate. Conclusions Eye movement parameters as currently reported by the HFA do not appear to be correlated with key sensitivity parameters when considering the repeatability of intrasession SITA‐Faster 24–2 VF results. Thus, current gaze tracker outputs do not appear to provide clinically meaningful information for interpretation of intra‐visit visual field results that cannot already be garnered using other strategies.